2018
DOI: 10.1155/2018/4839230
|View full text |Cite
|
Sign up to set email alerts
|

Benralizumab: From the Basic Mechanism of Action to the Potential Use in the Biological Therapy of Severe Eosinophilic Asthma

Abstract: Asthma is a very frequent chronic airway disease that includes many different clinical phenotypes and inflammatory patterns. In particular, eosinophilic bronchial inflammation is often associated with allergic as well as nonallergic asthma. The most important cytokine involved in the induction, maintenance, and amplification of airway eosinophilia in asthma is interleukin-5 (IL-5), released by both T helper 2 (Th2) lymphocytes and group 2 innate lymphoid cells (ILC2). Hence, IL-5 and its receptor are suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 76 publications
3
87
0
Order By: Relevance
“…6 IL-5 is a cytokine responsible for the growth, recruitment, activation, and proliferation of eosinophils, which are key mediators in reactive airway inflammation and disease, particularly in asthma. 7,8 The most common adverse events reported with mepolizumab administration are headache, injection-site reactions, back pain, and fatigue. 7,8 To our knowledge, this is the first case of non-cardiac chest pain associated with mepolizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 IL-5 is a cytokine responsible for the growth, recruitment, activation, and proliferation of eosinophils, which are key mediators in reactive airway inflammation and disease, particularly in asthma. 7,8 The most common adverse events reported with mepolizumab administration are headache, injection-site reactions, back pain, and fatigue. 7,8 To our knowledge, this is the first case of non-cardiac chest pain associated with mepolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The most common adverse events reported with mepolizumab administration are headache, injection-site reactions, back pain, and fatigue. 7,8 To our knowledge, this is the first case of non-cardiac chest pain associated with mepolizumab. Interestingly, in a previous clinical trial investigating the use of mepolizumab in exacerbations of refractory eosinophilic asthma, there was 1 patient who developed chest pain in the treatment group, whereas no patients in the placebo group reported chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…It selectively binds to free IgE, and thus decreases the expression of IgE receptors on mast cells/basophils, and dendritic cells . Anti‐IL‐5 biologics include mepolizumab, and benralizumab which binds to IL‐5 receptor leading to the induction of eosinophil and basophil apoptosis . Reslizumab is another anti‐IL‐5 monoclonal antibody and it is indicated in patients whose asthma is not adequately controlled via standard therapy.…”
Section: Types Of Biologicsmentioning
confidence: 99%
“…2,4,8 Anti-IL-5 biologics include mepolizumab, and benralizumab which binds to IL-5 receptor leading to the induction of eosinophil and basophil apoptosis. 9 Reslizumab is another anti-IL-5 monoclonal antibody and it is indicated in patients whose asthma is not adequately controlled via standard therapy. It is reportedly efficacious, well tolerated, and safe.…”
Section: Types Of Biologicsmentioning
confidence: 99%
“…These two trials (Corren, et al l and Bjermer, et al) demonstrated that reslizumab is more ef icacious in patients with severe eosinophilic asthma (blood eosinophil > 400 cells/μl) [30,31]. Brusselle, et al in their 2017 study, assessed the ef icacy of reslizumab in patients receiving baseline treatment per GINA step 4 and 5 guidelines, and found that reslizumab reduced the exacerbation rate by 53% (95% CI0.36-0.62) and 72% (95% CI 0.15 -0.52) in step 4 and step 5 groups respectively [32]. Several studies reported that because of the weight-based dosing strategy for reslizumab, it was more effective than a ixed dose mepolizumab in reducing sputum eosinophils and other asthma control outcomes [23,26].…”
Section: Il-5 Antagonistsmentioning
confidence: 99%